The Impact of Focus Group Discussion (FGD) And Video on Women Adult Knowledge, Attitudes, and Practices (KAP) of IVA Examination - Permaini, Titi; Perdani, Agni Laili; Melisa, Septi; Muhaimin, Toha; Anwar, Syamsul; Basri, Achmad Ali (Universitas Pendidikan Indonesia, 2023)
Introduction. The most common types of cancer among women adults are cervical cancer that can be prevented by doing IVA practice. One of the factors contributing to the low practice of women performing early detection through IVA is lack of knowledge. Action should be made to improve information through health promotion using various learning education combinations with technology and conventional methods with Focus Group Discussion (FGD) and creative videos. Objective. To explore the impact of innovative health education on women's adult knowledge, attitudes, and practice of IVA test examinations. Method. This research uses a quantitative quasi-experimental with a group pre-test and post-test design and divided into two intervention groups. Convenience sampling method was approached during two months of data collection from August-September 2023. A structured instrument was used to measure knowledge, attitudes, and practice (KAP). Result. The pre-test showed average knowledge value before the intervention was 1.95 and attitude was 0.45 and after the intervention, it was 9.80 and attitude 0.95, respectively. The statistical result showed a significant difference with a value of 0.000 (0.05). The practice of IVA test before was 5% and after the intervention was 90%. The FGD and video educational methods influence knowledge, attitudes, and practice of IVA tests. Discussion. The FGD and video educational methods influence knowledge, attitudes, and practice of IVA tests. There is a need to develop other educational methods combination between FGD and video to increase IVA test information therefore it will influence women adult interest in carrying out IVA tests as an effort to detect cervical cancer early.